Description of Stenotrophomonas sepilia sp. nov., isolated from blood culture of a hospitalized patient as a new member of Stenotrophomonas maltophilia complex. (September 2021) - Gautam, V.; Patil, P.P.; Bansal, K.; Kumar, S.; Kaur, A.; Singh, A.; Korpole, S.; Singhal, L.; Patil, P.B.
Abstract: Stenotrophomonas sepilia strain SM16975 (= JCM 32102; = KCTC 62052) is a new species isolated from the blood culture of a hospitalized patient. The biochemical characterization, phenotypic criteria, phylogenomic reconstruction, and genomic analysis were carried out to differentiate it from its phylogenetic neighbours, establishing novel species status in the genus Stenotrophomonas and within Stenotrophomonas maltophilia complex (Smc).